Socioeconomic inequality in rehabilitation service utilization for schizophrenia in China: Findings from a 7-year nationwide longitudinal study - Ding, Ruoxi; He, Ping; Zheng, Xiaoying (Frontiers in Psychiatry, 2022)
Aims Few studies have focused on the utilization of rehabilitation services among people with schizophrenia. In this study, we aimed to examine the trend of pharmacological and psychotherapy service utilization among adults with schizophrenia and to identify the associated socioeconomic factors. Methods Data were obtained from the Second National Sample Survey on Disability in 2006 and from the follow-up investigation in 2007–2013. Individuals with schizophrenia were ascertained by the combination of self-reports and on-site diagnosis by psychiatrists. Random effect logistic regression models were applied to examine the socioeconomic disparity in service utilization and the time trend in the association. Results Overall, the percentage of individuals using pharmacological treatment services increased from 23.7 in 2007 to 55.0% in 2013, and the percentage of individuals using psychotherapy services increased from 11.4 to 39.4%. Living in rural areas, being illiterate, living in families with lower income and being uninsured were less likely to receive pharmacological treatment and psychotherapy. The pace of growth in service utilization was higher among individuals with rural residence, illiteracy or low-income status than among their counterparts with advantaged backgrounds. Conclusions This study demonstrated an upward trend in pharmacological treatment and psychotherapy service utilization and a downward trend in socioeconomic disparity among Chinese adults with schizophrenia. Future studies to explore the reasons for the observed changes and to identify policies for improving the health service access of this vulnerable group are warranted.